Comparative Study of Metformin, N-Acetylcysteine and L-Arginine on Hyperglycemia in Streptozotocin-Induced Diabetic Rats - Bajwa, Novera Sohail; Aslam, M. Waqar; Amin, M. Roh ul; Abida Mateen A,; Saifullah Khan,; Ain, Qurat ul; Talha Laique, (Pakistan Journal of Medical & Health Sciences, 2022)
Diabetes mellitus (DM) is a chronic metabolic syndrome which results from deficiencies/defects in the pancreatic insulin secretions or insulin action on the target tissues. Purpose: To compare the beneficial effects of Metformin, N -acetylcysteine and L-arginine on dyslipidemia and hyperglycemia in Streptozotocin-induced diabetic rats. Study Design: Randomized controlled trial. Methodology: A total of 35 rats were used with 5 rats randomly allocated in 7 groups. Diabetic model was created by using streptozotocin (35 mg/kg) single dose intraperitoneal (IP). After 48 hours the animals with blood sugar concentration more than 300 mg/dl were considered diabetic. First group and second group were controls with Diabetic Mellitus (DM) rats. The group three, four and five with diabetic rats were given Metformin, N -acetylcysteine (NAC) and L-arginine (L-Arg) respectively. The sixth group of diabetic rats was given combination of Metformin and NAC while the seventh group of diabetic rats was given Metformin and L-Arg. All groups were treated for four weeks. At the end of the experimental period, groups were compared for fasting blood glucose. Statistical analysis: SPSS 25.0 statistical software was used to analyze the whole data. The difference between all the groups was analyzed using One-Way Analysis of Variance (ANOVA). Results: Significant improvement, with regards to the BSF test in L-Arginine Group, Metformin plus L-Arginine Group and the Metformin plus N-acetylcysteine group. Conclusion: It was concluded that in streptozotocin induced diabetic model, hyperglycaemia was significantly attenuated by the use of novel antioxidants; L-Arginine and N-acetylcysteine.